Application of herbal anaesthetics in aquaculture - Seyyed Morteza Hoseini; Ali Taheri Mirghaed; Morteza Yousefi (Wiley Publishing Asia Pty Ltd, 2025)
Anaesthesia is a widely used tool in fish handling, sampling and surgery in aquaculture; thus, fish anaesthesiology has been studied for a long time. In this case, there are several common anaesthetics in aquaculture, namely tricaine methanesulfonate (a chemical agent) and clove oil (a natural agent). Recently, there was an increasing interest to use herbal materials (other than clove oil) in fish anaesthesia. In this review, current knowledge about the use of herbal anaesthetics has been summarized. To date, essential oils/extracts of different plants have been studied for fish anaesthesia; most of them belong to Lamiaceae, Verbenaceae, Lauraceae and Myrtaceae. In addition, menthol, linalool, myrcene, cineole, globulol, spathulenol, guaiol, caryophyllene oxide, terpinen-4-ol and dehydrofukinone are herbal compounds that their anaesthetic effects have been studied in fish. Compared with clove oil and eugenol as the most common herbal anaesthetic, all tested herbal materials are less efficacious to anaesthetize fish. Some plants’ essential oil/extract, namely Aloysia triphylla, Myrcia sylvatica, Lippia alba and Curcuma longa, have beneficial health effects including suppression of physiological and oxidative stress. There is a lack of data in mechanism of anaesthesia and health effects of the herbal anaesthetics, which should be followed in future studies. In addition, most of the current studies have focused on certain fish species such as silver catfish (Rhamdia quelen), tambaqui (Colossoma macropomum) and common carp (Cyprinus carpio), and in most of the studies, essential oils/extracts of South American plants have been used. Thus, there is a need to study other fish and plant species.